Parameters influencing complaints and joint function in patients with osteochondral lesions of the ankle: an investigation based on data from the German Cartilage Registry (KnorpelRegister DGOU) - Körner, Daniel; Bangert, Yannic (Archives of orthopaedic and trauma surgery, 2017)
IntroductionPatients with osteochondral lesions of the ankle represent a heterogeneous population with traumatic, posttraumatic and idiopathic forms of this pathology, where the etiology of the idiopathic form is principally unknown. The aim of this study was to classify the heterogeneous patient population according to the patients’ complaints and joint function. Data from the German Cartilage Registry (KnorpelRegister DGOU) was analyzed for this purpose to investigate whether traumatic and posttraumatic lesions cause more complaints and loss of joint function than idiopathic lesions. Moreover, it was sought to determine if lesion localization, defective area, stage, patient age, gender, and body mass index (BMI) are related to patients’ complaints and loss of joint function.Materials and methodsA 117 patients with osteochondral lesions of the ankle were operated in 20 clinical centers in the period between October 2014 and January 2016. Data collection was performed by means of a web-based Remote Data Entry system at the time of surgery. Patients’ complaints and joint function were assessed with online questionnaires using the German versions of the Foot and Ankle Ability Measure (FAAM) and the Foot and Ankle Outcome Score (FAOS), followed by statistical data evaluation.ResultsNo significant difference was indicated between the groups with traumatic/posttraumatic lesions and idiopathic lesions with regard to most of the patients’ complaints and joint function, excluding the category Life quality of the FAOS score, where patients with idiopathic lesions had a significantly better quality of life (p = 0.02). No significant association was detected between lesion localization, defective area, patient age, gender, and BMI on the one hand, and patients’ complaints and joint function on the other. Similarly, no significant association was found between lesion stage according to the International Cartilage Repair Society (ICRS) classification and patients’ complaints and joint function. However, a higher lesion stage according to the classification of Berndt and Harty, modified by Loomer, was significantly associated with more complaints and loss of joint function in some categories of the FAAM and FAOS scores (p ≤ 0.04).ConclusionsEtiology of the lesion, lesion localization, defective area, lesion stage according to the ICRS classification, patient age, gender, and BMI do not seem to be of considerable relevance for prediction of patients’ complaints and loss of joint function in osteochondral lesions of the ankle. Using the classification of Berndt and Harty, modified by Loomer, seems to be more conclusive.